MEDIA PEMBELAJARAN BERBASIS RENDERFOREST PADA WORKSHOP GURU - Adirasa Hadi Prasetyo (Jurnal Pengabdian kepada Masyarakat (J-PMas), 2024)
This service activity aims to train teachers at SDN Murtajih 1 in creating learning media based on the Renderforest platform. Things that are trained in this workshop include: introduction to the Renderforest platform, selecting 3D Animation Toolkit templates, filling in images, adding music, materials and the conversion process to MP4 video format. This service was carried out by KKN (Real Work Lecture) lecturers and students to all teachers at SDN Murtajih 1, Pademawu District, Pamekasan Regency. This workshop aims to equip teachers with the ability to create innovative digital teaching media based on the Renderforest platform. Furthermore, the knowledge gained from this workshop activity can be used when engaging in actual learning activities.